Implementasi Metode Blended Learning Dalam Pembelajaran Geografi di SMA Negeri 2 Kota Bengkulu - Etika Sihaini; Mirna Yunita; Muhammad Alfi; Yuneva Yuneva; Warsa Sugandi Karman; Dedi Guntar (Universitas Prof. Dr. Hazairin, S.H, 2022)
At the beginning of 2020, the world was shocked by the Covid-19 pandemic which spread across the globe. In Indonesia, especially the education sector has been badly affected by this outbreak. As if having to adapt to a new learning routine, namely the distance learning system. However, distance learning has not been effectively implemented due to many limitations, especially in remote, underdeveloped, and remote areas. This study aimed to describe the implementation of blended learning as an alternative learning method at SMA Negeri 2 Bengkulu City during the Covid-19 pandemic, including inhibiting and supporting factors. The method used is a field research method with a descriptive qualitative approach. Data collection was carried out by means of observation, interviews, and documentation. The technique for determining informants used purposive sampling with research informants from school principals, geography teachers, and students. Data analysis in qualitative research according to Miles & Huberman with data reduction, data presentation, and conclusion/verification. The results of the study show that there are three stages of implementing blended learning, namely: the planning stage by designing learning objectives, preparing infrastructure, preparing learning schedules and face-to-face and online schedules, and compiling evaluation and socialization tools. The steps in carrying out online learning in an independent asynchronous manner, face to face in all subjects, especially learning geography. The stages of evaluating the learning system include teacher meeting activities with the school principal which are held once a month, and teacher and parent associations which are held once a semester. In this study, there are also several inhibiting and supporting factors for blended learning.